Design and Implementation of Nusa Medis for Cloud Computing-Based Electronic Medical Record Systems - Wahyu Wijaya Widiyanto; Mochammad Arief Darmawan; Rizka Licia (LPPM Politeknik Aceh Selatan, 2023)
The background of this research is the importance of using information technology in health services to increase the efficiency and effectiveness of health services. However, there are still many challenges in implementing electronic medical record systems, such as difficulties in integrating data from various sources, data security issues, and limitations in data accessibility. The purpose of this research is to design and implement a cloud computing-based electronic medical record system that can meet the special needs of various healthcare providers and improve the accessibility of patient data safely and efficiently. The method used in this study is a system development approach based on the software development life cycle by combining user-based design principles and feedback from healthcare providers. The result of this research is a web-based electronic medical record system that can be accessed from anywhere with an internet connection, with features such as medical history tracking, appointment scheduling, prescription management, and billing management. This system also has a high level of security to protect patient privacy and prevent unauthorized access.